Comparison of sludges produced from two different recirculating aquaculture systems (RAS) for recycle and disposal - Maigual-Enriquez, Yemall Alexander [UNESP]; Maia, Amanda Alves Domingos [UNESP]; Guerrero-Romero, Camilo Lenin; Matsumoto, Tsunao [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Morais, Leandro Cardoso de [UNESP] (Elsevier, 2019)
Sludges from Submerged Biofilter (SBF) and Aerobic Three Phase Airlift Fluidized Bed Reactor with Circulation in Concentric Tubes (AAFBR-CT) wastewater treatment of recirculating aquaculture systems (RAS) were evaluated by thermogravimetric analysis. It was considered a microstructural analysis by SEM-EDX and XRD to identify the sample composition. SBF and AAFBR-CT sludge, presented three stages for both combustion and pyrolysis. The first stage to 180 °C was characterized by loss of water, low-stability organic compounds, the second stage, between 235 °C and 385 °C was characterized by decomposition of carbohydrate, lipids, and proteins. The third stage, between 420 °C and 540 °C represents a decomposition of monounsaturated, polyunsaturated fatty acids and amino groups. This sludge had a high ash content and is not viable to use for energy purposes. Presence of granular material was revealed by SEM. XRD analysis only identified SiO2. The sludges generated by RAS could be used in brick and ceramic manufacture, adsorbent material or for phosphorus recovery.
Keywords: Biological Sludge; Combustion; Pyrolysis; Recirculating Aquaculture System; TG/DTG